IMPLEMENTASI ALGORITMA HARD MELOKALISASI FITUR WAJAH PADA CITRA WARNA - Juhardi, Ujang; Marhalim, Marhalim (Jurnal Sistem Informasi, 2018)
Face detection is one of the early stage is very important in a facial recognition system (face recognition) used in biometric identification. So far, the main obstacle in the face detection system revolves around the issue size (image resolution), the image resolution is the level of detail of an image. The higher the resolution the higher the level of detail of that image .Haar like Feature is a method commonly used in the detection of objects particularly the face detection and its features. Principle Haar-like features are simple to recognize objects based on the value of the feature but not the pixel values ​​of the image of that object. This method has the advantage that the computation is very fast, because it depends on the number of pixels in a square instead of each pixel value of an image. To implement and analyze speed haar algorithm results in a localized facial features of this research using MATLAB R2012b software in order to know how to analyze and implement and get the results to analyze the effect of image resolution algorithm localizes haar in the facial features (eyes, nose, and mouth). This research was carried out independently both secondary data collection and processing of data, for the data collection method in this study the authors use the method of literature and laboratory studies. Suggested the presence of this study, the authors hope to contribute to fellow-researcher  to examine other influences which affect the success haar algorithms, so the algorithm can be developed haar better